THEOCRATIC PRINCIPLES IN THE MISSIONARY SERVICE OF JESUS CHRIST: Seeking and Rescuing the Lost Based on Luke 19:10 - Ramlen Woran; Janes Sinaga; Juita Lusiana Sinambela; Steven Phang (QUAERENS: Journal of Theology and Christianity Studies, 2023)
The theocracy that introduced Jesus in Luke was more about the principles of God's government based on love. The book of Luke says the Son of Man came to seek and save the lost. He came not to condemn the world but so that the world, through Him, could be saved. This study explores the theocratic principles underlying Jesus Christ's missionary ministry, focusing on His efforts to seek and rescue the lost, as illustrated in Luke 19:10. The research method used is hermeneutics with a historical analysis and text context analysis approaches. Through a historical approach, this study aims to explore the principles of theocracy in Christ's missionary service throughout time. Analysis of texts and historical context will help identify changes, consistency, and continuity in the understanding and implementation of theocratic principles. The results are expected to provide deep insight into how theocratic principles played a key role in Christ's missionary service, taking into account changes and adaptations throughout history. The practical implications of this research include guidance for mission practitioners and church leaders in developing ministry strategies that take into account the historical course of theocratic principles in Christ's mission.